Synthesis and GABAA receptor activity of oxygen-bridged neurosteroid analogs - Alvarez, Lautaro Damian (2008)
Three analogs of neuroactive steroids were prepared (4–6) in which 1,11- or 11,19-oxygen bridges give a constrained conformation. Their 3D structures were obtained by ab initio calculations and in the case of 3α-hydroxy-11,19-epoxypregn-4-ene-20-one (4), confirmed by X-ray analysis. Biological activity of the synthetic steroids was assayed in vitro using t-[3H]butylbicycloorthobenzoate as radiolabeled ligand for the GABAA receptor. The activity of compound 4 was similar to that of allopregnanolone (1). 1α,11α-Epoxypregnanolone (6) was more active than pregnanolone (2).